A Dynamic Network Model of the Successor's Knowledge Construction From the Resource- and Knowledge-Based View of the Family Firm. (June 2018) - Cabrera-Suárez, M. Katiuska; García-Almeida, Desiderio Juan; De Saá-Pérez, Petra
The article initially addresses the concept of familiness and its connection with the succession process in the family firm to emphasize the relevance of the successor's knowledge. Then, a model is presented that evolves from a dyadic relationship in the knowledge transfer process from predecessor to successor to a network of exchanges with multiple agents and sources that enhance the successor's construction of knowledge through time. Key aspects derived from that model about the successor's human capital, the predecessor's role, the knowledge network, the relational context, and the time dimension of the process are then discussed.